Dari Rumah ke Altar : Kontribusi Orang Tua terhadap Spiritualitas dan Keterlibatan Orang Muda Katolik - Adelheit Awa Hurint; Vinsensius Bawa Toron; Petrus Tukan (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to examine the level of participation of Catholic Youth (OMK) in spiritual activities, identify the factors contributing to their low involvement, and formulate strategies that parents can implement to foster OMK's enthusiasm for church engagement. The research employs a descriptive qualitative approach, involving eight informants consisting of active OMK, inactive OMK, and their respective parents. Data were collected through interviews and observations, and analyzed in three stages: data reduction, data display, and conclusion drawing and verification.The findings reveal that active OMK demonstrate strong attendance at Mass, active involvement in youth leadership roles, and stable spiritual growth. In contrast, inactive OMK show low participation due to a lack of internal motivation and weak parental support. Active parents have a positive influence through their role modeling, shared prayer, and open communication about faith.In conclusion, parental involvement plays a critical role in shaping OMK's participation and spiritual development. A consistent approach to family-based spiritual formation is essential to encourage greater youth involvement in the life of the Church.